2011
DOI: 10.1634/theoncologist.2010-0268
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Chemotherapy for Operable Breast Cancer Improves Surgical Outcomes in the Community Hospital Setting

Abstract: Results. There were 212 patients included. Seventynine percent of patients who underwent PC had a clini-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
12
1
1
Order By: Relevance
“…Excision volumes in patients undergoing BCS after NACT were reported in fifteen studies, including two prospective cohort studies and thirteen retrospective studies [ 20 , 25 , 27 , 28 , 31 , 33 , 39 , 40 , 42 , 44 , 45 , 47 , 48 50 ]. Thirteen studies were single-center studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Excision volumes in patients undergoing BCS after NACT were reported in fifteen studies, including two prospective cohort studies and thirteen retrospective studies [ 20 , 25 , 27 , 28 , 31 , 33 , 39 , 40 , 42 , 44 , 45 , 47 , 48 50 ]. Thirteen studies were single-center studies.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with T2 or T3 tumors, the mean excision volume was significantly lower in patients who received chemotherapy preoperatively (113 cm 3 vs. 213 cm 3 , p = 0.0043) with no difference in tumor size at presentation [ 25 ]. Four retrospective studies that compared BCS with or without NACT reported conflicting results [ 27 , 28 , 31 , 33 ]. Two studies showed lower excision volumes after NACT (132.2 cm 3 vs. 158.1 cm 3 , p = 0.04 and 143.6 cm 3 vs. 273.9 cm 3 , p < 0.004) [ 27 , 28 ], whereas one study showed larger excision volumes following NACT (108 cm 3 vs. 78 cm 3 , p = 0.002) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…a taxa de margem limítrofe ou positiva foi reduzida à metade (23% versus 46%, p=0,04) e isso resultou em menos reexcisões (p=0,01). o volume de tecido removido também foi menor no grupo com quimioterapia neoadjuvante (143,6 cm 3 contra 273,9 cm 3 , p=0,003) 8 . esses autores também demonstraram que a aderência ("compliance") ao tratamento foi maior no grupo tratado com quimioterapia neoadjuvante versus adjuvante (100% versus 70%, p=0,0001) 9 .…”
Section: Resultsunclassified